Determinan Kejadian Stunting pada Anak Usia 0- 59 Bulan di Wilayah Kerja Puskesmas Dalu Sepuluh Desa Dalu 10 A Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Hilda Miranda Sejuk; Siti Khairani Novi Nurjanah; Masryana Siagian (Universitas Muhammadiyah Manado, 2025)
Stunting is a growth failure condition in toddlers caused by chronic malnutrition, making children shorter than their age. Stunting is a public health issue that requires serious attention due to its long-term impact on children’s development. Based on observations at Puskesmas Dalu Sepuluh, the prevalence of stunting was recorded at 52 children in 2022 and 35 children in 2023 out of a total of 6,737 toddlers. In addition, 8 children were identified as stunted during this research. This study aims to analyze the determinants of stunting in children aged 0–59 months in the working area of Puskesmas Dalu Sepuluh, Dalu 10 A Village, Tanjung Morawa District, Deli Serdang Regency. The research design used was observational analytic with a cross-sectional approach. The population consisted of 445 toddlers, and a sample of 211 respondents was selected using the Slovin formula with probability random sampling. Data were analyzed using the Chi-Square test, Fisher’s Exact test, and Multiple Logistic Regression Enter Method at a 95% confidence level. The findings showed that complementary feeding (OR = 9.13, 95% CI: 1.39–76.01) reduces the risk of stunting, while family income (OR = 12.92, 95% CI: 1.56–106.91) and parenting patterns (OR = 11.56, 95% CI: 1.39–96.01) increase the risk. Addressing these factors is vital to reduce stunting prevalence in toddlers.